Numerical study of double emulsion formation in microchannels by a ternary Lattice Boltzmann method. (2nd June 2016) - Fu, Yuhang; Zhao, Shufang; Bai, Lin; Jin, Yong; Cheng, Yi
Abstract: A ternary LBM model was successfully established to numerically investigate the double emulsion formation process in a flow-focusing microfluidic device. The model was validated by comparing the simulated interfacial phenomena in three-phase systems with the theoretical solutions, where physical properties of each fluid can be independently defined in the newly established LB model. Meanwhile, the numerical simulations showed good agreement of the double emulsion formation in different flow regimes with the experimental data in the literature. Especially for the three representative flow regimes, i.e., dripping, jetting and middle jet containing monodispersed inner drop, the model predictions show that the emulsion size follows scaling law in dripping regime. Effect of the viscosities of middle and inner fluids on the occurrence of flow regimes was further discussed, indicating that smaller viscosity of either middle or inner fluid should be beneficial to the double emulsion production. Highlights: Established a ternary Lattice Boltzmann method based on color-gradient model for multiphase flow simulations. Simulated contacting conditions of two immiscible droplets in another fluid by ternary color-gradient model. Predicted the flow regimes for double emulsion formation in microchannels. Presented the effects of viscosities of middle and inner fluids on the double emulsion formation.